The professional tasks of pediatric nurses according to parents of hospitalized children - Warmuz-Wancisiewicz, Aneta; Witanowska, Jolanta; Ufniarz, Paulina; Knapik, Andrzej; Stemplewska, Bożena; Jarecka, Beata (Nursing in the 21st Century, 2018)
THE PROFESSIONAL TASKS OF PEDIATRIC NURSES ACCORDING TO PARENTS OF HOSPITALIZED CHILDRENIntroduction. Steadily growing market of medical services currently presents the patient as a client of medical facility. Narrowing the medical market to the pediatric ward, apart from meeting the needs and care of the sick child, the main goal is a good opinion of the parent.Aim. The aim of the study was to obtain the opinions of parents of hospitalized children about the professional tasks of pediatric nurses.Materials and methods. The survey was conducted in the group of 60 parents of children hospitalized in pediatric wards with the use of authors’ own questionnaire.Results. The majority of respondents (80%) believe that the continuing presence of a parent in the hospital is beneficial for the medical treatment of the child. The number of 76.7% believe that their presence in the hospital makes the child not feeling lonely while suffering. As many as 93.3% of parents said that nurses explain them all doubts and that they attempt to work with them for the recovery of the child. When it comes to 90% of respondents, they said that the aid and information on the care of a sick child received from the nurses are sufficient. As many as 68.3% believe that the nursing staff has a high level of professional skills, and 93.3% – that nurses provide physical and mental safety to hospitalized children. When it comes to 91.7% of parents, they said that nurses have respectful approach to the little patients. The working conditions of nurses in the opinion of 68.3% of respondents have an impact on their child care.Conclusions. Caregivers positively evaluate the work done by nurses in the wards. Nurses spend with children the right amount of time. In the opinion of parents, working conditions of nurses have an impact on their work with the child. Most parents claim that the work of nurses is responsible, physically and mentally hard, and it requires patience and composure.